Shared genetic susceptibility of vascular-related biomarkers with ischemic and recurrent stroke. (26th January 2016) - Williams, Stephen R.; Hsu, Fang-Chi; Keene, Keith L.; Chen, Wei-Min; Nelson, Sarah; Southerland, Andrew M.; Madden, Ebony B.; Coull, Bruce; Gogarten, Stephanie M.; Furie, Karen L.; Dzhivhuho, Godfrey; Rowles, Joe L.; et al.
Abstract : Objective: To investigate the genetic contributors to cerebrovascular disease and variation in biomarkers of ischemic stroke. Methods: The Vitamin Intervention for Stroke Prevention Trial (VISP) was a randomized, controlled clinical trial of B vitamin supplementation to prevent recurrent stroke, myocardial infarction, or death. VISP collected baseline measures of C-reactive protein (CRP), fibrinogen, creatinine, prothrombin fragments F1+2, thrombin-antithrombin complex, and thrombomodulin prior to treatment initiation. Genome-wide association scans were conducted for these traits and follow-up replication analyses were performed. Results: We detected an association between CRP single nucleotide polymorphisms (SNPs) and circulating CRP levels (most associated SNP, rs2592902, p = 1.14 × 10 −9 ) in 2, 100 VISP participants. We discovered a novel association for CRP level in the AKR1D1 locus (rs2589998, p = 7.3 × 10 −8, approaching genome-wide significance) that also is an expression quantitative trait locus for CRP gene expression. We replicated previously identified associations of fibrinogen with SNPs in the FGB and LEPR loci. CRP-associated SNPs and CRP levels were significantly associated with risk of ischemic stroke and recurrent stroke in VISP as well as specific stroke subtypes in METASTROKE. Fibrinogen levels but not fibrinogen-associated SNPs were also found to be associated with recurrent stroke in VISP. Conclusions: Our data identify a genetic contribution to inflammatory and hemostatic biomarkers in a stroke population. Additionally, our results suggest shared genetic contributions to circulating CRP levels measured poststroke and risk for incident and recurrent ischemic stroke. These data broaden our understanding of genetic contributors to biomarker variation and ischemic stroke risk, which should be useful in clinical risk evaluation.